2019
DOI: 10.1108/ijchm-05-2018-0395
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of emotional labor research from the hospitality and tourism literature

Abstract: Purpose The purpose of this paper is to provide an exhaustive review of emotional labor research from the hospitality and tourism literature by outlining the theories, the antecedents and the outcomes of emotional labor, as well as the underlying mechanisms (i.e. mediators and moderators) of emotional labor. Design/methodology/approach This study provides a qualitative and critical review of emotional labor research from the hospitality and tourism literature, providing insights into the trends and gaps in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 56 publications
1
99
0
12
Order By: Relevance
“…The preferred instrument used to measure emotional intelligence, emotional labor and job satisfaction in this study was a questionnaire. The constructs used in this research have been mainly studied using quantitative methods, using instruments whose reliability and validity have been attested to in previous research (Acosta-Prado and Zárate-Torres, 2019; Eşitti and Kasap, 2020; Khairy, 2020; Lee and Madera, 2019; Li et al., 2018; Pacheco et al., 2019; Viseu et al., 2020; Wang, 2019), so this tool was considered as the best for reaching the goals of the study in an effective manner. Moreover, the questionnaire method enables the gathering of a larger amount of data, using already validated survey scales and ensuring the anonymity of respondents (which is of particular importance when researching job-related issues, when employees may not feel comfortable providing honest answers).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The preferred instrument used to measure emotional intelligence, emotional labor and job satisfaction in this study was a questionnaire. The constructs used in this research have been mainly studied using quantitative methods, using instruments whose reliability and validity have been attested to in previous research (Acosta-Prado and Zárate-Torres, 2019; Eşitti and Kasap, 2020; Khairy, 2020; Lee and Madera, 2019; Li et al., 2018; Pacheco et al., 2019; Viseu et al., 2020; Wang, 2019), so this tool was considered as the best for reaching the goals of the study in an effective manner. Moreover, the questionnaire method enables the gathering of a larger amount of data, using already validated survey scales and ensuring the anonymity of respondents (which is of particular importance when researching job-related issues, when employees may not feel comfortable providing honest answers).…”
Section: Methodsmentioning
confidence: 99%
“…Lee and Madera (2019) reviewed the literature on emotional labor in tourism and hospitality and found that emotional intelligence was frequently studied as an antecedent of emotional labor, along with the influence of personality traits, but that the mediating effects of emotional intelligence on the relationship between emotional labor and other factors had not been explored. This analysis was confirmed in a meta-analysis by Xu et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface acting refers to an employee emotional regulation strategy that modifies external expressions, whereas deep acting refers to the emotional regulation strategy genuinely feel the emotions that are required and expected. Even though extant literature has found that emotional labor predicts multiple employee well-being and performance constructs (Hülsheger & Schewe, 2011; Kammeyer-Mueller et al, 2013; L. Lee & Madera, 2019), most previous studies consider emotional labor (i.e., surface acting and deep acting) as a static, trait-like construct and largely focuses on examining the intrapersonal effect of emotional labor on employees’ well-being or performance.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the Example 2 highlighted that ESM can examine the within-person component of constructs (e.g., surface acting and deep acting) that are considered as static and trait-like in an existed theory (e.g., emotional labor theory; Grandey, 2000). Most of the previous emotional labor studies in hospitality research treated employees’ surface acting and deep acting as between-individual constructs that are stable over time (Hülsheger & Schewe, 2011; Kammeyer-Mueller et al, 2013; L. Lee & Madera, 2019).…”
Section: Introductionmentioning
confidence: 99%